2018
DOI: 10.1080/01616846.2018.1555412
|View full text |Cite
|
Sign up to set email alerts
|

Information Provision by Public Library to Agricultural Extension Agents in a Developing Country

Abstract: One of the bedrock of Sustainable Development Goals (SDGs) is eradication of poverty and hunger. In an attempt to actualize this goal, the role of public libraries in information provision to agricultural extension agents in Nigeria becomes paramount. This paper discusses provision of information to agricultural extension agents in a developing country. It starts with the concept of extension agents and the essence of information provision to them. It further discusses types, sources and challenges of public l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Public libraries (58.4%) and academic libraries (48.6%) were the most preferred libraries for farmers to get agricultural information. This finding agreed with Jerome et al (2018) and ISO ( 2013), which stated that public libraries were established to provide information for local people, mostly extension workers and farmers, to boost productivity. Also, almost all the farmers in the study areas have positive attitudes toward the perceived roles of libraries, such as repackaging agricultural information, presentation of agricultural documentaries, and use of ICT tools to enhance free access to existing databases by farmers, such as Global Online Research in Agriculture (AGORA) and The Essential Agricultural Library (TEEAL).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Public libraries (58.4%) and academic libraries (48.6%) were the most preferred libraries for farmers to get agricultural information. This finding agreed with Jerome et al (2018) and ISO ( 2013), which stated that public libraries were established to provide information for local people, mostly extension workers and farmers, to boost productivity. Also, almost all the farmers in the study areas have positive attitudes toward the perceived roles of libraries, such as repackaging agricultural information, presentation of agricultural documentaries, and use of ICT tools to enhance free access to existing databases by farmers, such as Global Online Research in Agriculture (AGORA) and The Essential Agricultural Library (TEEAL).…”
Section: Discussionsupporting
confidence: 88%
“…It is usually financed, in whole or in part, from public funds, and its basic services are free of charge or available for a subsidized fee. Services rendered by public libraries, such as information repackaging, translation, presentation of documentaries through videos, and literacy programs, among others, are the pivots that extension programs could rest upon to ensure and deployment of innovations that could boost the productivity of rural farmers who need information, which is now a very important factor of production (Jerome, Ayotunde, Chidi, Ayooluwa, Sola, and Toluwa, 2018). Also, ISO (International Organization for Standardization), ( 2013) found that the largest percentage of respondents used public libraries to provide information for local people, mostly extension workers and farmers.…”
Section: Various Libraries Used As Information Sources By Farmersmentioning
confidence: 99%
“…Comparatively, the result reveals that extension personnel in Anambra State earns approximately N4000.00 higher than their counterparts in Ebonyi State. This result aligns with the observation of [9] [34], and [35], who noted that agricultural extension workers in Nigeria are poorly remunerated. This financial predicament may adversely affect the motivation and willingness to embrace innovations that could enhance organisational performance or their ability to invest in acquiring digital technologies or devices and skills without external support.…”
Section: • Socioeconomic Characteristics Of Agricultural Extension Pe...supporting
confidence: 92%
“…This is not unconnected to prolonged adverse economic conditions, limitations in budgetary provision, infrastructural and political challenges facing these countries as well as inadequate technical-know required for the deployment and usage of modern working tools and technologies involved within LMS. Other factors include high cost of ICT equipment, lack of ICT strategies and policies, frequent Power Outages and poor maintenance culture [14,15,16,17].…”
Section: Challenges Hindering the Adoption Of Lms In Developing Comentioning
confidence: 99%